Spatial Patterns and Composition Traits of Soil Microbial Nitrogen-Metabolism Genes in the Robinia pseudoacacia Forests at a Regional Scale - Ku, Yongli; Lei, Yuting; Han, Xiaoting; Peng, Jieying; Zhu, Ying; Zhao, Zhong (Frontiers in Microbiology, 2022)
Microbial-driven processes related to the nitrogen-metabolism (N-metabolism) in soil are critical for ecosystem functioning and stability. There are spatial patterns of microbial-mediated nitrogen processes, but we still lack an overview of the soil N-metabolism genes of single nitrogen-fixing tree species pure forests at a regional scale. Here, we investigated the spatial variation and drivers of microbial N-metabolism genes in the rhizosphere soil of Robinia pseudoacacia on the Loess Plateau by metagenomic technology. We found that the distance-decay of soil N functional gene similarities in Robinia pseudoacacia forests on the Loess Plateau spanning a geographic distance of 230 km was significant (p<0.001). The gene composition and co-occurrence patterns in the process of soil microbial N-metabolism were very different, and they were mainly driven by soil pH and MAP. The proportion of positive links and edges co-occurrence networks between N functional genes increased with increasing pH, suggesting that increasing pH promoted connections between functional genes. The relative frequencies of N-metabolism pathways were consistent on the Loess Plateau, the abundance of ammonia assimilation pathway was highest, and the abundance of the nitrogen fixation pathway was the lowest; only the abundance of the nitrogen fixation pathway was not significantly different. The geographical patterns of the N-metabolism microbial species compositions (genus and species levels) were obvious, and there was niche separation. There was functional redundancy in N functional genes at the regional scale. The bacterial and archaeal communities involved in soil nitrogen metabolism were significantly different, and the main driving factors were the MAP and nitrate nitrogen content, respectively. Structural equation modeling showed that decreases in soil pH and MAP mainly affected the increase in nitrogen functional gene abundance through an increase in the diversity of N-metabolism microorganisms. In conclusion, this study provides a baseline for biogeographic studies of soil microbe functional genes.